Exotic states of diatomic molecules and methods of their description - Kowalczyk, Paweł; Jastrzębski, Włodzimierz; Pashov, Asen (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
Various methods for representation of electronic states in diatomic molecules basing on experimental spectroscopic data are critically compared. The technique of pointwise inverted perturbation approach (IPA) is indicated as the most suitable in case of states characterized by potential energy curves substantially different from the Morse potential. Recent developments of this technique are presented.
Optica Applicata, Vol. 36, 2006, nr 4, s. 511-522
Keywords: optyka; diatomic molecules; potential energy curves; inverted perturbation approach; molecular spectra